2008
DOI: 10.1093/ndt/gfn381
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with early recovery of kidney injury after vascular surgery and improved long-term outcome

Abstract: Statin use is associated with improved recovery from AKI after major surgery and has a beneficial effect on long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 28 publications
4
49
0
2
Order By: Relevance
“…This is also true for statins. First reports on its usefulness were not supported by the following studies [168][169][170][171] . It has been known since 2001 that low-dose dopamine is not justified for the prevention and treatment of AKI [172,173] .…”
Section: Pharmacological Interventionsmentioning
confidence: 90%
“…This is also true for statins. First reports on its usefulness were not supported by the following studies [168][169][170][171] . It has been known since 2001 that low-dose dopamine is not justified for the prevention and treatment of AKI [172,173] .…”
Section: Pharmacological Interventionsmentioning
confidence: 90%
“…17 In reality, patients with symptomatic PAD are at particularly high risk for having CKD. Feringa et al, 2 found that in patients with decreased (50.9) ankle-brachial index (ABI), 42% had mild, 22% had moderate and 3% had severe chronic kidney disease, amounting about two-thirds of patients with PAD, and statin use and ACEI has been reported to decrease or to slow the progression of CKD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies have shown that statins are associated with less AKI, whereas others have not. [15][16][17][18][19][20][21] Their potential benefit in the perioperative setting has also been shown in some small randomized controlled trials where administration of statins preopera-tively improved cardiovascular outcomes. 22,23 To examine the issue further and to inform the conduct of definitive randomized controlled trials, we studied all older patients who underwent major elective surgery in Ontario, the largest province in Canada, over a 14-year period.…”
mentioning
confidence: 89%